The influence of brand experience, brand trust and brand image on brand loyalty in Apple Iphone users - Melinda Alfiananda; Edy Purwo Saputro (Jurnal Mantik, 2024)
In this era of digital, smartphones, especially Apple's iPhone, have become a key element in everyday life, Apple's iPhone has played a special role by making a significant contribution to the evolution of communication technology. Therefore, the purpose of this study is to explore the effect of brand experience, brand trust, and brand image on consumer brand loyalty using Apple iPhone products. The research method applied is quantitative research, by taking a population of all Apple iPhone brand users in the Faculty of Economics and Business, Universitas Muhammadiyah Surakarta. The sample of this study amounted to 120 respondents, selected through sampling techniques, using purposive sampling method as an approach to non-probability sampling technique. The data collection and analysis process was carried out using the Smart-PLS 3.0 application. The results showed that brand experience, brand trust, and brand image positively influence the level of consumer brand loyalty for Apple iPhone products